The Relationship Between Online Game Addiction And Emotional Changes In Adolescents In Class VII SMPN 7 Palangka Raya - Muhammad Rolan Rahmatilah; Melisa Frisilia; Stefanicia Stefanicia (PROMOTOR, 2026)
Background: Adolescent online gaming addiction has emerged as a serious concern in the field of social and psychological research. It has the potential to cause emotional changes, such as irritability, social withdrawal, or difficulty controlling emotions. With high internet access but minimal supervision, adolescents can be exposed to the negative effects of online gaming, which can also affect their academic performance and social relationships. Objective: To determine and analyze the relationship between online gaming addiction and emotional changes in seventh-grade adolescents at SMPN 7 Palangka Raya City. Methods: This study used a correlational quantitative design with a cross-sectional approach. A sample of 59 students was selected through a simple random sampling technique. Data collection used an online game addiction questionnaire and a Guttman scale-based emotional change questionnaire. Data analysis was performed using the Spearman Rank test. Results: The results of the Spearman Rank test showed a p-value of 0.001 <α 0.05, which means that there is a significant relationship between addiction to playing online games and emotional changes in seventh-grade students of SMPN 7 Palangka Raya City. Conclusion: There is a significant relationship between addiction to playing online games and emotional changes in adolescent children. Collaborative efforts between schools, parents, and community health workers are needed to prevent the impact of online gaming addiction.